2014
DOI: 10.1093/jscr/rju032
|View full text |Cite
|
Sign up to set email alerts
|

Mediastinal emphysema following fracture of the orbital floor

Abstract: Pneumomediastinum (PM) is mainly an atypical finding among traumatic neck or thoracic injury patients. Moreover, PM secondary to isolated orbital floor fracture remains a rare event which is infrequently associated with severe complications such as mediastinitis, airway obstruction and pneumothorax. Herein, we report an atypical case of mediastinal emphysema consequent to orbital floor fracture along with review of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 11 publications
0
12
0
1
Order By: Relevance
“…In 2011 Rapp et al [34] analyzed nearly 70,000 elderly for falls that occurred in residences in Germany and observed a higher frequency of falls among male patients, and approximately 75% of the events occurred in the bedroom or bathroom. A previous study with a small sample size showed that elderly who sustained falls-related injury at bathroom were significantly associated with the female gender and high mortality rate [35].…”
Section: Discussionmentioning
confidence: 98%
“…In 2011 Rapp et al [34] analyzed nearly 70,000 elderly for falls that occurred in residences in Germany and observed a higher frequency of falls among male patients, and approximately 75% of the events occurred in the bedroom or bathroom. A previous study with a small sample size showed that elderly who sustained falls-related injury at bathroom were significantly associated with the female gender and high mortality rate [35].…”
Section: Discussionmentioning
confidence: 98%
“…The unilateral facial emphysema increased over time as the patient sneezed and subsequently involved the neck spaces and chest wall down to the mediastinum implicating the endoscopic sinus surgery as a possible cause of the disease. Facial air collection can spread to the infratemporal fossa or the retropharyngeal and parapharyngeal spaces, and because the mediastinum has a good connection with the sublingual, submandibular, retropharyngeal and parapharyngeal spaces, and with the neck vessel sheaths, the facial air collection can disperse through these planes and find its way down to the mediastinum [9], [10].…”
Section: Discussionmentioning
confidence: 99%
“…The lesion directly continues through the muscular inner layer of the buccinator muscle sublingual and submandibular spaces which are also connected with retropharyngeal, parapharyngeal, and pterygomandibular spaces. A subcutaneous air collection in the malar area, a possible consequence of orbital-maxillo-zygomatic complex fracture, can also spread to infratemporal fossa or to retropharyngeal, parapharyngeal, and pterygomandibular spaces [1,4,6,7]. An unusual origin of facial emphysema and even pneumomediastinum is the so-called pneumoparotitis.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of extensive pneumomediastinum, even pneumoperitoneum can therefore occur [12]. Other causes of subcutaneous emphysema and pneumomediastinum in trauma patients could be penetrating wounds, esophageal and tracheal rupture (including tracheostomy and endotracheal intubation), or infections caused by anaerobic bacteria with secondary aerobic bacteria colonization of the air collection [1,2,4,8,13]. Finally in some rare cases, pneumomediastinum can arise without any obvious portal and so-called idiopathic pneumomediastinum [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation